Growing up in the gutter diaspora & comics - Quintana-Vallejo, Ricardo (The University of Arizona Press, 2024)
"Growing Up in the Gutter: Diaspora and Comics is the first book-length exploration of contemporary graphic coming-of-age narratives written in the context of diasporic and immigrant communities in the United States by and for young, BIPOC, LGBTQ , and diasporic readers. The book analyzes the complex identity formation of first- and subsequent-generation diasporic protagonists in globalized rural and urban environments and dissects the implications that marginalized formative processes have for the tercentennial genre in its graphic version."
Keywords: Erwachsenwerden -- Motiv; LGBT -- Motiv; Graphic Novel; Diaspora -- Sozialwissenschaften, Motiv; USA; Graphic novels / United States / History and criticism; Bildungsromans / History and criticism; American literature / Minority authors / History and criticism; American literature / 21st century / History and criticism; Minorities in literature; Graphic novels; United States; 2000-2099; Criticism, interpretation, etc